OPERATIONAL EFFICIENCY AS A MEDIATOR OF FEE-BASED AND NON-FEE-BASED REVENUE ON THE OPERATIONAL PERFORMANCE OF LISTED SECURITIES COMPANIES ON THE INDONESIA STOCK EXCHANGE - Ujang Syaiful Hidayat (Universitas 17 Agustus 1945 Surabaya, 2026)
This study aims to examine the effect of revenue structure on the operational performance of securities firms while considering the mediating role of operational efficiency. Revenue structure is represented by fee-based income and non-fee-based income, whilst operational performance is measured using operational profitability indicators. This study adopts a quantitative approach utilizing the PLS-SEM technique with SmartPLS. The data were drawn from the financial statements of listed securities firms covering the 2022–2024 period. The findings reveal that both fee-based and non-fee-based income do not exert a significant direct impact on operational performance. However, operational efficiency was found to positively mediate the influence of both types of income on operational performance, albeit at a low level of significance. These findings indicate that revenue structure does not automatically improve operational performance without being supported by the company’s ability to manage cost efficiency and internal processes. This study underscores the importance of operational efficiency as an internal mechanism bridging revenue strategy and the achievement of operational performance in securities firms, particularly within the post-pandemic market dynamics.